(untitled) (Journal of Biomedical Investigation, 2025)
Background: The consumption of groundnut oil and palm oil have become common in our daily diets. These oils are edible vegetable oils widely consumed globally and are composed of saturated and unsaturated fatty acids. While these oils are often promoted for their perceived health benefits, emerging research suggests potential implications for lipid profiles. They are said to be pro atherogenic and can be responsible for cardiovascular complications. Aim: This study was aimed to assess the comparative effects of groundnut oil and palm oil on lipid profile of Wistar Rats. Materials and Methods: Fifteen (15) Adults Wistar rats weighing between 90-100g were procured for this study. They were divided into three (3) groups of five (5) rats each. All the animals were given rat chow and normal saline ad libitum. The Control group (Group 1) was given rat chow and normal saline only. The Sample groups; Group 2 was administered with 100mg/kg of groundnut oil while Group 3 was given 100mg/kg of palm oil for 21 days. The weight of the animals before and after the administration were recorded. Results: Increase in body weight was seen across all the groups (both control and sample). The average body weights of the control group, Group 2 and Group 3 were 110, 115 and 119 grams respectively which indicates that the sample groups were significantly different when compared with the control group (P˂0.05). That of sample group 2 indicates a statistically significant difference in relation to sample group 3 (P˂0.05). The Control group (Group 1) had the lowest cholesterol level (70.01±0.03 mg/dl) while the rats administered groundnut oil (Group 2) had the highest cholesterol level (100.07±0.17 mg/dl). The cholesterol level of the rats administered with palm oil (Group 3) was (85.50±0.07 mg/dl). The Control group had the highest value for HDL (110.78±0.06 mg/dl), followed by Group 3 (89.66±0.02 mg/dl) while Group 2 had the least HDL level (80.50±0.06 mg/dl). The triglyceride and LDL levels were highest in Group 3 (100.92±0.02 mg/dl and 90.78±0.04 mg/dl respectively), followed by Group 2 (80.87±0.07 mg/dl and 80.70±0.06 mg/dl respectively). Group 1 had the lowest triglyceride and LDL levels (70.80±0.00 mg/dl and 72.48±0.48 mg/dl respectively). Conclusion: Groundnut oil was seen to increase the lipid profile more than the palm oil. Excessive intake of these vegetable oils should be avoided to prevent elevated lipid profile which may predispose an individual to cardiovascular diseases. Keywords: Palm oil, Groundnut oil, Body weight, Lipid profile, cardiovascular diseases.